2007
DOI: 10.1016/j.abb.2006.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an alternative splice variant of human nucleoside triphosphate diphosphohydrolase 3 (NTPDase3): A possible modulator of nucleotidase activity and purinergic signaling

Abstract: Nucleoside triphosphate diphosphohydrolase 3 (NTPDase3) is a cell surface, membrane-bound enzyme that hydrolyzes extracellular nucleotides, thereby modulating purinergic signaling. An alternatively spliced variant of NTPDase3 was obtained and analyzed. This alternatively spliced variant, termed "NTPDase3β", is produced through the use of an alternative terminal exon (exon 11) in place of the terminal exon (exon 12) in the full-length NTPDase3, now termed "NTPDase3α". This results in an expressed protein lackin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…For construction of ER-targeted NTPDase3, we deleted the C-terminal part of the cytosolic tail in the wild-type enzyme which is not necessary for normal processing or activity of NTPDase3 (31), and added the ER targeting signal from the wheat germ agglutinin binding protein 1 (WBP1, (16)) together with the hemagglutinin (HA) epitope and a spacer (Fig. 2 A ).…”
Section: Resultsmentioning
confidence: 99%
“…For construction of ER-targeted NTPDase3, we deleted the C-terminal part of the cytosolic tail in the wild-type enzyme which is not necessary for normal processing or activity of NTPDase3 (31), and added the ER targeting signal from the wheat germ agglutinin binding protein 1 (WBP1, (16)) together with the hemagglutinin (HA) epitope and a spacer (Fig. 2 A ).…”
Section: Resultsmentioning
confidence: 99%
“…This restriction prevents use of the common epitope mapping approach for making truncated proteins because truncation of anything more than the short C-terminal cytoplasmic tail portion (i.e. the A511Stop mutant) [54] results in NTPDase3 proteins that are misfolded and enzymatically inactive, and thus not recognized by the inhibitory monoclonal antibodies (data not shown). Therefore, we used two other approaches to define the monoclonal antibody epitope: (a) introduction of cysteine residues by mutagenesis followed by chemical cleavage of native NTPDase3 with NTCB at the introduced residues and (b) disruption of individual disulfide bonds by mutagenesis.…”
Section: Discussionmentioning
confidence: 99%
“…NTPDase3β was expressed and targeted to the membrane; however, it had no measurable activity. When COS cells were co-transfected with the cDNAs of NTPDase3α and 3β, the amount of the active NTPDase3α delivered to the plasma membrane was reduced [90]. These results suggested that NTPDase3β may play a role in regulating NTPDase3α activity and purinergic signaling in tissues that express both proteins.…”
Section: Cr3 Acr3mentioning
confidence: 94%